Getting it right : Notre Dame on leadership and judgment in business - Bartkus, Viva Ona.; Conlon, E. J. (Edward J.), 1951- (San Francisco : Jossey-Bass, 2008)
"To be a successful business leader, executives need to make values-based problem solving a habit of mind, argue management experts and Notre Dame professors Viva Ona Bartkus and Ed Conlon. In Getting It Right, Bartkus and Conlon draw on insights from consulting, management, and academia to deliver a powerful message: no matter how chaotic the marketplace, leaders can still address even the most staggering challenges and problems in a calm and confident manner. The authors present the problem-solving framework that has formed the basis of Notre Dame's business education and has been tested in corporate settings. The model encompasses three overarching themes; discovering solutions, moving from analysis to action, and driving solutions through the organization."--BOOK JACKET.
Starting from values -- What really is the problem here? -- Priorities -- One percent inspiration -- Ninety-nine percent perspiration -- How to tell the story -- The business case -- When good enough is both -- Frailty, fortitude, and a leader's commitment -- Bulldoze the barriers -- Toils of sisyphus.
Includes bibliographical references (p. 279-280) and index.
Keywords: Problem solving; Leadership; Decision making